KNIFE-EDGE MODIFIED SUBGINGIVAL CROWN PREPARATION: DENTAL PREPARATION ACCORDING TO BIOLOGICAL PRINCIPLES - Hudyono, Rikko; Fathurrahman, Helmi; Elok, Nafisah; Anggarani, Welly; Putranto, Rama (Odonto : Dental Journal, 2024)
Fixed bridge and crown restorations are widely utilized in dental practice. The utilization of bridge as a substitute for implants is prevalent in several contexts. The crown preparation procedure has a crucial role in determining the long-term periodontal tissue health. Under-preparation frequently manifests in many clinical circumstances, resulting in the thickening of the prosthetic crown in the cervical region. The accumulation of plaque in subgingival preparations is an often seen issue. Given the progressive advancements in material technology and manufacturing procedures, it is imperative to critically evaluate the continued suitability of chamfer and shoulder preparation techniques in contemporary practice. This is particularly relevant when considering restorations involving subgingival preparation edges. The objective of this study is to examine the utilization of knife-edge modified subgingival preparation procedures and monolithic zirconia restorative materials as potential strategies for the maintenance of periodontal and esthetic tissues over an extended length of time